Cuproptosis patterns and tumor immune infiltration characterization in colorectal cancer - Du, Yan; Lin, Yilin; Wang, Bo; Li, Yang; Xu, Duo; Gan, Lin; Xiong, Xiaoyu; Hou, Sen; Chen, Shuang; Shen, Zhanlong; Ye, Yingjiang (Frontiers in Genetics, 2022)
Abstract Faced with the high heterogeneity and poor prognosis of colorectal cancer(CRC), this study sought to find new predictive prognostic strategies to improve the situation. Cuproptosis is a novel cell death mechanism that relies on copper regulation. However, the role of cuproptosis-related gene (CRG) in CRC remains to be elucidated. In this study, we comprehensively assessed the CRG landscape in CRC based on The Cancer Genome Atlas (TCGA). We identified differential expression and genetic alterations of CRG in CRC. CRG is highly correlated with initiation, progression, prognosis, and immune infiltration of CRC. We construct a risk score signature containing 3 CRGs based on LASSO. We explored the correlation of CRG-Score with clinicopathological features of CRC. Age, stage, and CRG-Score were integrated to construct a nomogram. The nomogram has robust predictive performance. We also understand the correlation of CRG-Score with CRC immune landscape. CRG-Score can effectively predict the immune landscape of CRC patients. Low-risk CRC patients have greater immunogenicity and higher immune checkpoint expression. Low-risk CRC patients may be better candidates for immunotherapy. At the same time, we also predicted more sensitive drugs in the high-risk CRC patients. In conclusion, the CRG risk score signature is a strong prognostic marker and may help provide new insights into the treatment of individuals with CRC.